Reading philosophy, writing poetry : intertextual modes of making meaning in early medieval China - Swartz, Wendy, 1972- (Cambridge, Massachusetts : Published by the Harvard University Asia Center, 2018)
""In a formative period of Chinese culture, early medieval writers made extensive use of a diverse set of resources, in which such major philosophical classics as Laozi, Zhuangzi, and Classic of Changes featured prominently. Reading Philosophy, Writing Poetry examines how these writers understood and manipulated a shared intellectual lexicon to produce meaning. Focusing on works by some of the most important and innovative poets of.
Reading and writing in early medieval China -- Xi Kang and the poetics of bricolage -- The poetic repertoire of Sun Chuo -- The Lanting Excursion and Xuanyan poetry -- The "spontaneous" poet Tao Yuanming as an intertext -- Reading and roaming the landscape: the classic of changes in Xie Lingyun's poetry.
eBooks on EBSCOhost
Keywords: Chinese poetry -- 220-589 -- History and criticism; Chinese literature -- Philosophy; Intertextuality; Poésie chinoise -- 220-589 -- Histoire et critique; Littérature chinoise -- Philosophie; Intertextualité.; Chinese literature -- Philosophy; Chinese poetry; Intertextuality; 220-589; Criticism, interpretation, etc